ENVIRONMENTAL DEGRADATION AS THE IMPACT OF CAPITALIST INTEREST AND THE LACK OF PUBLIC AWARENESS IN SPONGEBOB'S LAST STAND MOVIE - KURNIAWAN, ARIF (Jurnal Ilmiah Mahasiswa FIB, 2014)
Kurniawan, Arif. 2014. Environmental Degradation as the Impact of Capitalist Interest andthe Lack of Public Awareness in SpongeBob’s Last Stand Movie. Study Program of English,Universitas Brawijaya.Supervisor: Yusri Fajar, Co-supervisor: Winda Candra Hantari.Keywords: environmental degradation, public awareness, capitalism, SpongeBob’s Last Standmovie.Environmental problems are threatening human life in this world now. Environmentalproblems cause an imbalance between human and nature. One of the environmental problems isenvironmental degradation caused by capitalist interest and lack of public awareness. Theproblem is reflected in SpongeBob’s Last Stand movie as a reflection to the reality now. Thereare two problems to be solved in this study; (1) how capitalist interest results in environmentaldegradation and what the impacts of that interest toward environment; (2) how far the awarenessof people in the movie toward the environment.This study uses ecocriticism as the main theory to analyze this movie. This study alsouses a concept of capitalism and movie studies.The result of the study finds that environmental degradation causes many impacts to thewhole city. In the movie, Plankton as the capitalist builds a highway which crossing JellyfishField as the greenest place in Bikini Bottom. All people approve it without realizing the impactafter that. SpongeBob who disagrees with the highway struggles to stop it but it is vain. Jellyfishas the main occupant of Jellyfish Field take revenge to the whole city because their habitat isdestroyed by them. A great chaos is in the city. Everybody gets the impact for what they havedone.A study about environment is very important and interesting. SpongeBob as an animationmovie has many stories telling about environmental problems. It is good for the next researcherto keep on studying environment from many aspects to find solution for environmental problems.